If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5g+20=-2g
We simplify the equation to the form, which is simple to understand
-5g+20=-2g
We move all terms containing g to the left and all other terms to the right.
-5g+2g=-20
We simplify left and right side of the equation.
-3g=-20
We divide both sides of the equation by -3 to get g.
g=6.6666666666667
| .33x+15=.50-12 | | 0.8x+0.2x= | | 3(x+13)=3x+39 | | c^2-5c=-2 | | -18x-9=9 | | 7x-11=4x+4 | | 9(x-10)=-x | | -6g+6=-5g+2g | | 7(x+8)=7(x+13) | | 2(x+y)=8 | | 11x=2(4x+39) | | 272=w+(2w+10) | | 5x+3x+4x=4x+2x | | 16x+4+3x+11+110=180 | | 7x+1-x=1+2x | | 1/7x^2 | | 11x=2(3x+75) | | 3(2x-2)+6y=0 | | 8(2+5m)=216 | | 8+8k=6k+9 | | 394=5m | | 2(4x-2)=3(2x-1) | | 17x=3(3x+40) | | 2.4*16= | | c^2-5c+2=0 | | -6x+12=-30 | | 4+2(5+(-3))= | | 5x^2=-2-11x | | 72x^3-80x^4= | | 3.25+0.25(v)=14 | | 3y-3+4x-2=3x+3y-1 | | 7p=-5m |